2011
DOI: 10.1002/ccd.22903
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous coronary intervention of left main pseudoaneurysm with customized covered stents

Abstract: Left main pseuodaneurysm is a rare entity and is one of the potentially lethal consequences of coronary artery dissection. We describe a case of a young woman who almost a week after her delivery developed spontaneous left main dissection, manifested as acute anterior myocardial infarction. Left on medical treatment alone over a month, spontaneous dissection progressed to symptomatic large left main pseuodaneurysm, which was treated percutaneously with covered stents. © 2011 Wiley-Liss, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Exclusion of duplicate results and articles not meeting specified a priori criteria (162 articles) resulted in 111 articles describing 138 cases of P-SCAD [5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [38], [39], [40], [41], [42], [43], [44], [45], [46], [47], [48], [49], [50], [51], [52], [53], [54], [55], [56], [57], [58], [59], [60], [61], [62], [63], [64], [65], [66], [67], [68], [69], [70], [71], [72], [73], [74], [75], [76], [77], [78], [79], [80], [81], [82], [83], [84], [85], [86], [87], [88], [89], …”
Section: Methodsmentioning
confidence: 99%
“…Exclusion of duplicate results and articles not meeting specified a priori criteria (162 articles) resulted in 111 articles describing 138 cases of P-SCAD [5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [38], [39], [40], [41], [42], [43], [44], [45], [46], [47], [48], [49], [50], [51], [52], [53], [54], [55], [56], [57], [58], [59], [60], [61], [62], [63], [64], [65], [66], [67], [68], [69], [70], [71], [72], [73], [74], [75], [76], [77], [78], [79], [80], [81], [82], [83], [84], [85], [86], [87], [88], [89], …”
Section: Methodsmentioning
confidence: 99%
“…Dhakam, et al reported that PCI with covered stent was used successfully to treat a coronary artery pseudoaneurysm. 6) In our case, however, PCI was unlikely to be recommended when we took the location of the aneurysm into consideration. The most common surgical technique may involve ligation of an aneurysm and distal bypass, which was described for the treatment of a left main coronary artery aneurysm.…”
Section: Pseudoaneurysm Following Percutaneous Coronary Interventionmentioning
confidence: 68%
“…4 More recently, covered stents have been used to occlude aneurysm and pseudoaneurysm in coronary arteries 14 and vein grafts. 15 Similarly, as a recent alternative to open surgical closure of pseudoaneurysms of the cardiac chambers, there are reports of successful interventional percutaneous techniques of implanting septal occluder devices in atria and ventricles.…”
Section: Treatmentsmentioning
confidence: 99%